Landslide Vulnerability Analysis Due to Earthquake Based on Seismic Vulnerability and Slope of the Slip Surface in Tritis, Yogyakarta: Ferdinandus Edwin Wiranata - Ferdinandus Edwin Wiranata Ferdinandus Edwin Wiranata (Jurnal Fisika dan Aplikasinya, 2021)
Tritis is a hamlet in Kulon Progo Regency, located in an area with steep slope topography making it vulnerable to landslides. Ground movement vulnerability due to earthquakes is controlled by several factors, one of which is the seismic vulnerability index whose value can be obtained through microtremor measurements by H/V analysis. In addition, the dynamic trigger factor for landslides is the slope. The slope of the surface is not always the same as the slope of the slip surface because it is observed from the surface, while the slip surface is under the soil layer and requires measurements using the geophysical method to determine the surface model. For this reason, an analysis is needed to compare the landslide vulnerability between these two factors, the slope of the surface and the slope of the slip surface. From the measurement results, there is a significant difference between the slope and the slope of the slip surface at the same site in the north of the slope by 15.17 with a seismic vulnerability index (kg) of 2.5. The distribution of seismic vulnerability index in all slopes ranges from 0.075 to 7.33, dominated by areas with slopes > 18. High landslide vulnerability is in the southern and northern areas.